Combined structural and theoretical investigation on differently substituted bispidine ligands: predicting the properties of their corresponding coordination polymers. Issue 18 (21st April 2020) - Lippi, Martina; Caputo, Josefina; Famulari, Antonino; Sacchetti, Alessandro; Castellano, Carlo; Meneghetti, Fiorella; Martí-Rujas, Javier; Cametti, Massimo
Abstract : Pyridine-based bispidine ligands L1–L7 have been studied by single crystal X-ray diffraction and solid-state DFT calculations in an attempt to predict the dynamic properties of their corresponding Mn(ii ) coordination polymers. Abstract : Pyridine-based bispidine ligands L1–L7, which differ in the substituent at the N 7 position of the bispidine scaffold, have been studied by single crystal X-ray diffraction and density functional theory (DFT) calculations, also including solid-state algorithms. Qualitative description of the packing interactions and quantitative data on the stability of each ligand in the solid-state have been employed to draw reasonable predictions on the ligand potential for the formation of linear 1D coordination polymers (CPs) with Mn(ii )Cl2 and on their resulting dynamic properties, in terms of adsorption and solvent exchange capabilities. The basic assumption lies in the fact that volume and polarizability of the ligands would similarly affect packing energies in both molecular solids and CP materials. The results here obtained confirm the data previously reported on CPs (those made from L4 are less dynamic than the ones with L1 ), but they also allow the prediction that CPs made with L2 and L5 should be more dynamic than expected, while CPs with L6 and L7 should not form altogether. This latter prediction was derived from the analysis of the steric and electronic factors of the ligand substituents on the N 7 position and it is further substantiated by the obtainment of a 2 : 1 molecular complex, and not a CP, by crystallization of L6 with MnCl2 .